Organizational Politics and Workplace Conflict in Selected Tertiary Institutions in Edo State, Nigeria - Samaila, Mande; Uzochukwu, Onyeizugbe Chinedu; Ishaq, Musah (International Journal of Emerging Trends in Social Sciences, 2018)
The increasing rate of organisational politics and workplace conflict has been a great challenge to tertiary institutions in Edo State. This study examined how organisational politics affects workplace conflict among tertiary institutions in Edo State. The objective of this study is to examine the relationship that exists between self-interest and communication breakdown of selected tertiary institutions in Edo State. A total number of 369 copies questionnaire were administered to the respondents domiciled in the six selected tertiary institutions under study (University of Benin, Benin city, Institute of Technology and Management, Usen, Ambrose Alli University, Ekpoma, College of Education, Igueben, Auchi Polytechnic, Auchi, Institute of Physical and Health Education, Afuze) using purposive sampling technique and 343 copies of questionnaire were retrieved from the respondents. The study was guided by one research question and one hypothesis, correlational design was adopted. The data used was primary data collected through a structured questionnaire. The data collected was presented using descriptive statistics and the hypothesis was tested using Pearson product moment correlation with the aid of statistical package for social science (SPSS version 21). The findings revealed that there is a significant positive relationship between self-interest and communication breakdown among the selected tertiary institutions in Edo State and the study concluded that organisational politics will definitely lead to workplace conflict if not properly managed. The study recommended that the management of tertiary institutions should put more effort in the supervision of staff so as to reduce the rate of organisational politics which is expected to increase employee performance, effective communication and employee output in the long run.